Laboratory static hardness tests - Goh, Jason Jia Sheng (Nanyang Technological University, 2023)
The objective of Laboratory Static Hardness Tests is to review and provide guidance on the Vickers Hardness Test. Hardness testing is used to obtain the hardness value of a material. Hardness value is an important material property used in various large sectors of engineering. This report focuses on the theory and process of determining the hardness value through Vickers Hardness Testing in accordance with the American Society for Testing and Materials (ASTM) E92 testing standards and guidelines. After the Vickers Hardness Test process, the report will discuss the significance and uses of hardness value to hardness value conversion tables as per ASTM E140 standards, as well as hardness value to tensile strength conversion tables as per International Organization for Standardization (ISO) 18625 standards and how to perform these conversions. Lastly, insight and recommendations based on experiences and observations during the duration of the project will be provided to address possible limitations of the Vickers Hardness Test.